Case Study of a Post-Cesarean Section Patient at Risk of Several Complications - Nuraeni, Imel; Widiasih, Restuning (Universitas Padjadjaran, 2024)
Childbirth is a natural process for women, but some conditions, exceptionally high risks, might elevate the likelihood of difficulties during pregnancy, childbirth, or afterwards. Maternal age, primiparity, and Cesarean section delivery provide a risk for several problems in the mother. This case study aims to examine and implement nursing care for primigravida mothers at high risk who have undergone a Cesarean section. The stages of a case study involve defining the case, selecting a case, gathering and analyzing data, interpreting data, and presenting results. Data collection involved interviews and physical examinations, reviewing health documentation, Talking with patients and families, and gathering information from other healthcare professionals. Data analysis included examining the collected data, identifying critical information, comparing the data, and presenting a summary in the form of a case study. Outcome: A 39-year-old primiparous woman who underwent a Cesarean section reported postpartum bleeding of approximately 1000 cc/24 hours, anaemia, emotional instability, and difficulty in caring for her baby and fulfilling her responsibilities. Nurses perform nursing interventions to address complications, such as preventing bleeding, treating anaemia, promoting relaxation for emotional stability, providing education through engaging and comprehensible media, and enhancing the mother’s role, particularly in breastfeeding, through hypno-breastfeeding techniques. Pregnant women with risk factors who undergo Cesarean sections are known to experience both physical and psychological difficulties. Effective nursing interventions that address physical and psychological elements, new roles, and prevention of complications lead to successful resolution of the issue, allowing the mother and infant to be discharged in good health